Phosphodiesterase inhibitors - Schudt, Christian; Dent, Gordon; Rabe, Klaus F.; ScienceDirect eBooks (San Diego : Academic Press, 1996)
Non-selective inhibitors of cyclic nucleotide phosphodiesterase (PDE), such as theophylline, have been used extensively since 1958. In the decade of the '70s, various PDE isoenzymes were defined which led to the development of the second generation of PDE inhibitors. Currently a variety of these new inhibitors are under test as potential anti-inflammatory drugs. During the past five years, molecular biology has revealed a superfamily of these phosphodiesterase isoenzymes. This book summarizes the present state of knowledge, as well as giving a comprehensive description of the compounds available. It will be invaluable for everyone who wants to choose the most suitable PDE inhibitor for their research or who is dealing with such drugs in a clinical setting. Key Features * Utilizes actual testing and research of new PDE inhibitors * Valuable for researchers and students alike.
Identification and quantification of PDE isoenzymes and subtypes by molecular biological methods -- Analysis of PDE isoenzyme profiles in cells and tissues by pharmacological methods -- Effects of theophylline and non-selective xanthine derivatives on PDE isoenzymes nad cellular function -- Ca2+/calmodulin-dependent cyclic nucleotide phosphodiesterase (PDEI) -- EHNA as an inhibitor of PDE2; a pharmacological and biochemical study in cardiac myocytes -- cGMP-inhibited phosphodiesterases (PDE3) -- Interaction of PDE4 inhibitors with enzymes and cell functions -- Inhibition of phosphodiesterase isoenzymes and cell function by selective PDE5 inhibitors -- Design and synthesis of xanthines and cyclic GMP analogues as potent inhibitors of PDE5 -- Enzymatic and functional aspects of dual-selective PDE3/4 inhibitors -- An isoform-selective inhibitor of cyclic AMP-specific phosphodiesterase (PDE4) with anti-inflammatory properties -- Characterization of different states of PDE4 by rolipram and RP 73041 -- Molecular aspects of inhibitor interaction with PDE4.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Elsevier
Keywords: Phosphodiesterases -- Inhibitors; Phosphodiesterases -- Inhibitors -- Therapeutic use; Phosphodiesterase Inhibitors -- pharmacology; Phosphodiesterase Inhibitors -- therapeutic use; MEDICAL -- Biochemistry; MEDICAL -- Pharmacology; Aufsatzsammlung; Immunpharmakologie; Inhibitor; Phosphodiesterasen; Electronic books